2016
DOI: 10.1002/jrs.5072
|View full text |Cite
|
Sign up to set email alerts
|

On the identification of folium by SERS: from crude extracts to illuminated codices

Abstract: The ancient purple dye known as folium is still a mystery for both scientists and art historians. Today, it is commonly assumed that folium was produced from the fruits of Chrozophora tinctoria (L.) A. Juss., a plant belonging to the Euphorbiaceae family, and efforts have been mainly devoted to highlight the analytical features of the dyes extracted from this plant, whereas detection in ancient manuscripts has been mainly based on poorly selective, non‐invasive analytical techniques. As a consequence, the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The main text of the manuscript was written in iron-gall ink (typical raising in the NIR region); shell gold (inflection point at 510 nm) was used for some initials. The palette of the illuminations is typical of 15thcentury miniature painting in Northern Europe, except for the use of folium that was more characteristic of Italian and southern French miniature schools [8,9].…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…The main text of the manuscript was written in iron-gall ink (typical raising in the NIR region); shell gold (inflection point at 510 nm) was used for some initials. The palette of the illuminations is typical of 15thcentury miniature painting in Northern Europe, except for the use of folium that was more characteristic of Italian and southern French miniature schools [8,9].…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…The behavior of the dyes as SERS probes was investigated in order to set up an accurate and selective procedure for the identification of dyes in ancient artworks. By unambiguously detecting the dye by SERS in the microsample of a medieval manuscript, they also demonstrated that the purple dye mentioned in ancient treatises is definitely linked with the aqueous extract from purple fruits of Chrozophora tinctoria . Campos‐Vallette et al studied the SERS spectra of red dyes in the Mapuche belts from the beginning of the 20th century.…”
Section: Art and Archaeologymentioning
confidence: 99%
“…By unambiguously detecting the dye by SERS in the microsample of a medieval manuscript, they also demonstrated that the purple dye mentioned in ancient treatises is definitely linked with the aqueous extract from purple fruits of Chrozophora tinctoria. [128] Campos-Vallette et al studied the SERS spectra of red dyes in the Mapuche belts from the beginning of the 20th century. Red dyes were stored in Museo Regional de la Araucania, Chile, and were investigated by using UVvisible absorption, liquid chromatography coupled to mass spectrometry, and Raman and SERS spectroscopies.…”
Section: Pigments Dyes Paints Fibres and Inksmentioning
confidence: 99%
“…Similarly, Fourier transform infrared spectroscopy (FTIR) is affected by the presence of the binder and the inorganic substrate of the lake, the signals of which are predominant over those of any dye, while Raman spectroscopy suffers from the problem of fluorescence emission associated with organic molecules. Also, since illuminated manuscripts are extremely delicate artifacts, it is discouraged (and generally prohibited by conservators) to take a sample that can be fully characterized by laboratory techniques widely used for dye identification, such as liquid chromatography combined with mass spectrometry (HPLC-MS) and SERS (surface-enhanced Raman spectroscopy), although these techniques have also been applied in some cases to the identification of dyes used in illuminated manuscripts [1][2][3][4][5]. As a non-invasive analytical method for this purpose, fiber optics reflectance spectroscopy (FORS) has been widely used [6][7][8][9], although this technique, based on electronic spectra, lacks the specificity typical, for example, of vibrational spectroscopy [10].…”
Section: Introductionmentioning
confidence: 99%